2014
DOI: 10.1139/cjfr-2013-0163
|View full text |Cite
|
Sign up to set email alerts
|

Growth and wood properties of genetically improved loblolly pine: propagation type comparison and genetic parameters

Abstract: The use of clonal varieties in forestry offers great potential to improve growth traits (quantity) and wood properties (quality) of loblolly pine (Pinus taeda L.). Loblolly pine trees established via somatic embryogenesis (clones), full-sib zygotic crosses, and half-sib zygotic open-pollinated families were sampled to identify variation in growth and wood properties among and within clonal lines and zygotic controls. Increment cores 5 mm in diameter were collected at age 4 from a total of 2615 trees. Growth pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…From the 1940's to the 2000's, improvement in silvicultural practices greatly increased estimated productivity of P. taeda plantations grown in the species' native range in the southeastern United States (Fox et al, 2007). There is evidence that maximum growth for the species in its native range is about 16 Mg ha −1 yr −1 (mean annual increment) (40 m 3 ha −1 yr −1 , assuming 400 kg m −3 wood density (Antony et al, 2014)) given that additional silvicultural inputs do not increase productivity beyond this amount (Zhao et al, 2016). Typical mean annual growth rates for P. taeda in the southeastern United States range from 16 to 33 m 3 ha −1 yr −1 (Zhao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…From the 1940's to the 2000's, improvement in silvicultural practices greatly increased estimated productivity of P. taeda plantations grown in the species' native range in the southeastern United States (Fox et al, 2007). There is evidence that maximum growth for the species in its native range is about 16 Mg ha −1 yr −1 (mean annual increment) (40 m 3 ha −1 yr −1 , assuming 400 kg m −3 wood density (Antony et al, 2014)) given that additional silvicultural inputs do not increase productivity beyond this amount (Zhao et al, 2016). Typical mean annual growth rates for P. taeda in the southeastern United States range from 16 to 33 m 3 ha −1 yr −1 (Zhao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Auty et al [38] found that incorporating annual ring width into a wood density model for Scots pine improved the predictive performance, and here we hypothesize that a ring width term could serve as a surrogate for silvicultural treatments, thereby allowing for adjustments to the SG or other wood properties-based growth rates. Although beyond the scope of this study, the impact of genetics on wood properties is a growing area of interest given the heritability of many wood properties and the ability to select families that have both fast growth and high wood density [40,50,51]. Finally, of additional importance are models for ring width, which when combined with ring SG models can yield whole disk SG values throughout the rotation that are particularly relevant to growth and yield decision support systems.…”
Section: Introductionmentioning
confidence: 99%
“…Wood quality traits were recently targeted as a breeding objective due to increasing demands for high-quality timber in the last 10 years. To advance the multi-trait breeding process, it is essential to profile the breeding parents/materials using either clonal testing or progeny trials, of which, clonal testing has proven to be a straightforward and effective strategy [13][14][15][16]. In the present study, to identify the variation and correlation in growth, wood property traits, and strobili number, 62 Chinese fir breeding parents were subjected to a 12-year grafted clone test with an eventual goal to select the best potential parent clones for future breeding programs.…”
Section: Introductionmentioning
confidence: 99%